Bedside critical ultrasound as a key to the diagnosis of obstructive atelectasis complicated with acute cor pulmonale and differentiation from pulmonary embolism: A case report. Issue 5 (14th March 2022) - Zhao, Haotian; Yan, Yaru; Liu, Yi; Long, Ling; Xue, Hongyuan; Zhao, Heling
Abstract: Acute attack of dyspnea may be combined with acute cor pulmonale (ACP). Rapid and accurate identification of the etiology of ACP is the key to its diagnosis and treatment. Echocardiography is a better imaging tool in the assessment of right ventricular function. Under the guidance of the theory of cardiopulmonary interaction, ultrasonography can detect lung lesions, which causes ACP. We report the case of a 67‐year‐old man who received mechanical ventilation for acute respiratory failure. Right ventricular dysfunction was detected by echocardiography. Lung ultrasound showed a high risk of pulmonary embolism. However, obstructive atelectasis should not be ruled out after increasing back area ultrasonography. To avoid pitfalls, combined cardiac and lung ultrasound should be used carefully and strictly. Abstract : Cardiac and lung ultrasound examination is a convenient and effective diagnostic tool for patients with respiratory or circulatory dysfunction. However, the ability to interpret ultrasound images and the differential diagnosis of diseases should be strictly studied and accurately mastered